The devil is a part-timer! 19 - Wagahara, Satoshi (The devil is a part-timer (graphic novels), 2022)
"Maou charges through a life-and-death battle to bring Emilia and Alciel back to Japan. Meanwhile, the objective of Gabriel and the Angels, as well as their hitherto unknown past forms, is finally revealed"--Back cover.